Fatores que aumentam a condição de vacas repetidoras em um rebanho leiteiro mestiço submetido à protocolos de sincronização reprodutivos - Souza, Fransergio; Cesar, João; Carneiro, Luisa Cunha [UNESP]; dos Santos, Ricarda Maria (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2016)
The objective of this study was to evaluate the incidence of repeat breeder (RB) in crossbred dairy cows submitted to a timed artificial insemination (TAI) and estrous synchronization protocols. Data from 371 heifers and 997 lactating crossbred dairy cows were analyzed. Cows with more than 30 DPP with good uterine condition, no lameness or clinical mastitis, and body condition score ≥ 2.5 were used. The cows were divided between two groups, as: group 1: TAI – those cows with no CL at ultrasound exam that were enrolled in a TAI protocol and group 2: estrous synchronization – all those cows that had CL. The incidences of RB and factors relative to it were analyzed by logistic regression in SAS. The incidence of RB condition was higher in lactating cows than nonlactating heifers (P < 0.001). There was a tendency of RB condition to higher in cows that calved during spring/summer than those calved at autumn/winter season. The parturition condition had no effect on RB incidence (P > 0.001); however, lactation degree influenced the incidence of RB (P <0.001). Repeat breeder condition was greater in lactating crossbred dairy cows than in heifers. Moreover, the presence of RB cows was higher in those from second parity group when compared to those from first, third and four parity groups; on the other hand, parturition condition did not influence the appearance of RB cows in the herd.
Factors that enhance repeat breeder condition in a crossbred dairy herd submitted to reproductive synchronization protocols
Keywords: Fertility; Parity; Reproduction; Season